2023
DOI: 10.47836/pjtas.46.2.01
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenicity of Aeromonas hydrophila in High-value Native Pangasius Catfish, Pangasius nasutus (Bleeker)

Abstract: Pangasius catfish, Pangasius nasutus, is a promising candidate for aquaculture due to its high market value. However, the presence of pathogenic bacteria in Aeromonas hydrophila is a major concern in P. nasutus farming in this country. This study determines the pathogenicity of A. hydrophila in P. nasutus. A total of 80 P. nasutus juveniles were intraperitoneally injected with 0, 103, 105, and 107 CFU mL-1 of A. hydrophila and monitored until 240 hr. The infected moribund fish’s kidneys, livers, and spleens we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 28 publications
1
0
0
Order By: Relevance
“…Likewise, Li, [77] found 100% similarity in the phylogenetic relationships of the 16S rRNA gene of A. hydrophila in China. In a recent study, Sani,[93] also observed 100% similarity in the phylogenetic relationships of the 16S rRNA gene of A. hydrophila in Malaysia, which corroborated our results.…”
Section: Plos Onesupporting
confidence: 90%
“…Likewise, Li, [77] found 100% similarity in the phylogenetic relationships of the 16S rRNA gene of A. hydrophila in China. In a recent study, Sani,[93] also observed 100% similarity in the phylogenetic relationships of the 16S rRNA gene of A. hydrophila in Malaysia, which corroborated our results.…”
Section: Plos Onesupporting
confidence: 90%